Razones para jugar: hacia la comprensión del rol del juego en el proceso de formación de docentes de educación inicial - Mendívil Trelles de Peña, Luzmila (2009)
The article aims to justify the need to reorient the teacher education process in order to produce changes in the educational practices in early childhood education level. From a critical perspective, it questions the theoretical career education away from life and concrete experiences of children, rethinking the centrality of play in the initial formation, not only as a theoretical reference carried out to improve learning processes, as it is in effect human and social life. At the same time, it emphasizes the emotional component as a key of change processes.